artikel Strategi Pemasaran Galeri Tenun Desa Setanggor Dalam Meningkatkan Daya Saing Penjualan Kain Tenun Di Wilayah Praya Barat Lombok Tengah. - Surianingsih Surianingsih; Dewi Rispawati; Siti Yulianah M. Yusuf (Distribusi - Journal of Management and Business, 2023)
This research is entitled "Marketing Strategy for the Setanggor Village Weaving Gallery in Increasing the Competitiveness of Sales Woven Fabrics in the West Praya Region, Central Lombok", which aims to determine the Marketing Strategy for the Setanggor Village Weaving Gallery in increasing the competitiveness of sales Woven Fabrics in the West Praya region, Central Lombok. The method used in this research is descriptive research with a qualitative approach. Data collection techniques are through interviews, observation and documentation. Data analysis in research uses SWOT analysis. The results of the research show that the Marketing Strategy carried out by the Setanggor Village Weaving Gallery in increasing the competitiveness of sales woven fabrics in the West Praya region of Central Lombok based on its position in Quadrant I in the SWOT Analysis is an aggressive strategy using more aggressive promotional strategies in promoting Village Songket Woven fabrics. Setanggor, so that it is better known by the public and abroad, which can be done through social media, websites, as well as variations in Setanggor Village Songket Woven cloth motifs that can adapt to current fashion. Keywords: Weaving Gallery, Marketing Strategy, Setanggor Village.